2020
DOI: 10.3389/fpubh.2020.00518
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of the Oxazolidinone Resistance–Associated Genes cfr and optrA in Enterococcus faecalis From a Healthy Piglet in Brazil

Abstract: Oxazolidinones are one of the most important antimicrobials potentially active against glycopeptide-and β-lactam-resistant Gram-positive pathogens. Linezolid-the first oxazolidinone to be approved for clinical use in 2000 by the US Food and Drug Administration-and the newer molecule in the class, tedizolid, inhibit protein synthesis by suppressing the formation of the 70S ribosomal complex in bacteria. Over the past two decades, transferable oxazolidinone resistance genes, in particular cfr and optrA, have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Furthermore, molecular investigations have allowed the detection of the LNZ resistance gene, cfr (D), in all phenotypical resistant E. faecium and E. gallinarum . This gene has recently been described as a new variant of the cfr gene in E. faecium from human clinical isolates in France, Ireland, the Netherlands, and Australia [ 25 , 26 , 27 , 28 ], and in E. faecalis from Spanish hospital isolates [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, molecular investigations have allowed the detection of the LNZ resistance gene, cfr (D), in all phenotypical resistant E. faecium and E. gallinarum . This gene has recently been described as a new variant of the cfr gene in E. faecium from human clinical isolates in France, Ireland, the Netherlands, and Australia [ 25 , 26 , 27 , 28 ], and in E. faecalis from Spanish hospital isolates [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This view may be supported by the observation that plasmids of the pLS20 family are all harbored by different Bacillus species, suggesting that they have a narrow host range [ 31 ]. Consistent with this view, the Inc18 plasmids are known to have a very broad host range [ 43 , 62 , 63 , 64 ]. It has been shown that the plasmids pIP501 and pAMβ1 can be introduced by conjugation into a wide variety of Gram-positive bacteria, and that the conjugation systems of these plasmids are functional in non-native hosts [ 43 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 89%
“…FloR and cfr were carried in the Tn 7 -like structure, which indicated that Tn 7 -like elements might play a role in mediating floR and cfr transmission. Tn 558 has been an important dissemination media of optrA and has been reported all over the world ( Tsilipounidaki et al, 2019 ; Almeida et al, 2020a , b ). Tn 558 normally surrounds optrA and mediates their transfer ( He et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%